Neuropsychological outcome of indoor rehabilitation in post-COVID-19 condition—results of the PoCoRe study - Jöbges, Michael; Tempfli, Melanie; Kohl, Christoph; Herrmann, Christoph; Kelm, Stefan; Kupferschmitt, Alexa; Montanari, Ida; Walter, Nike; Suetfels, Gerhard; Loew, Thomas; Köllner, Volker; Hinterberger, Thilo (Frontiers in Neurology, 2025)
BackgroundPost COVID-19 condition (PCC) is increasingly recognized as a debilitating condition characterized by persistent symptoms following SARS-CoV-2 infection. Neuropsychological deficits, including cognitive impairments and fatigue, are prevalent in individuals with PCC. The PoCoRe study aimed to evaluate the burden of neuropsychological deficits in PCC patients undergoing multidisciplinary indoor rehabilitation and to describe possible changes in this symptomatology.MethodsThe PoCoRe study, a prospective, non-randomized, controlled longitudinal study, recruited PCC patients from six German indoor rehabilitation centers. Eligible participants underwent comprehensive neuropsychological assessments at admission and discharge. Various measures were employed, including the fatigue scale for motor functioning and cognition (FSMC), the Test Battery for Attention (TAP) and the Montreal Cognitive Assessment (MoCA).ResultsOut of the 1,086 recruited participants, a total of N = 701 participants were included in the main data analysis. The prevalence of fatigue on admission was high (84.6%) and decreased significantly by discharge (77.4%), with a mild effect size. Reaction times on the alertness subtest were abnormal in 70% of patients on admission and 50% on discharge. Sustained attention was abnormal in 55% of patients on admission, decreasing to 43% on discharge. These differences were significant with mild effect sizes. Furthermore, of the 27% of participants with pathological MoCA scores at admission, 63% improved to normative levels during rehabilitation, indicating a significant treatment effect (p ≤ 0.001). However, the MoCA demonstrated limited sensitivity in detecting attention deficits.ConclusionThe PoCoRe study highlights the high prevalence of neuropsychological deficits and fatigue in PCC patients, with notable improvements observed following multidisciplinary rehabilitation. Challenges remain in accurately identifying and addressing these deficits, underscoring the importance of comprehensive neuropsychological assessment and tailored rehabilitation interventions. Further research is warranted to optimize screening tools and enhance neuropsychological care for PCC patients in both rehabilitation and outpatient settings.